DILIC: aplicação para ensino de conceitos de lógica de programação para crianças de três a seis anos - Júnior, Paulo Sérgio Atávila (Universidade Federal do Tocantins, 2021)
Learning programming is not just about having the knowledge of programming computers, or knowing several languages of programming, it also alters and broadens one’s percep tion of the world. Programming stimulates the development of children, because several skills are worked out, like: communication, problem solving, creativity development, etc. However, the teaching of programming for children has technological tools that still are very expensive and with little supply, because the niche in which they work is still new. Therefore, the goal of this paper was to develop an application for Apple iPadTM with the purpose to stimulate the learning of logic programming in children, aged three to six years old. The Primo CubettoTM kit, based on the Montessori methodology, is a tool to help children in the literacy period to learn concepts of logic programming, but it is still an expensive resource to adopt in schools in developing countries, like Brazil. The Cubetto was used as reference for the development of the Dilic application (Digital Literacy for Children), the result of this work. However, for the e↵ectiveness of this type of applica tion, it is necessary to develop an interface based on human-machine interface research, aimed at children in the age group studied, which was the main problem confronted in this research. Throughout the work, 27 guidelines and 12 desirable system requirements have been raised in the literature to be contemplated in application interfaces directed to children. The result of the research was the development of a low-cost application that can contribute to the popularization to the teaching of programming logic for children in schools around the world.